2006
DOI: 10.1080/14649350600673047
|View full text |Cite
|
Sign up to set email alerts
|

Calling Time: Managing Activities in Space and Time in the Evening/Night-time Economy

Abstract: Recent years have seen the emergence of two policy objectives and associated development trends in UK city centres relating to urban vitality and to the urban renaissance policy agenda. These involve a shift towards more city centre residential development and, associated with the 24-Hour City agenda, a shift towards the development of evening/night-time economies (ENTEs). Mixed land uses are seen as an essential component of this vitality. But conflicts often arise from different land uses in close proximity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…These findings echo complaints made in an earlier study (Comedia, 1991), which found similar patterns of town centres dominated by drunken youths at night whilst being relatively abandoned by older people. This pattern of avoidance has both temporal and spatial dimensions, with the early part of the evening posing fewer problems than the period around midnight and the early hours of the morning (Tiesdell & Slater, 2006). In addition to age, gender is also a factor and Scraton and Watson (1998) found that some younger women stayed away from the 'bright lights of the postmodern city' as exemplified by Leeds city centre.…”
Section: Contextmentioning
confidence: 96%
“…These findings echo complaints made in an earlier study (Comedia, 1991), which found similar patterns of town centres dominated by drunken youths at night whilst being relatively abandoned by older people. This pattern of avoidance has both temporal and spatial dimensions, with the early part of the evening posing fewer problems than the period around midnight and the early hours of the morning (Tiesdell & Slater, 2006). In addition to age, gender is also a factor and Scraton and Watson (1998) found that some younger women stayed away from the 'bright lights of the postmodern city' as exemplified by Leeds city centre.…”
Section: Contextmentioning
confidence: 96%
“…Temporary use of specific outdoor urban areas is permitted by the Singapore government, as evidenced by the unlicensed, ethnic vendor stands appearing at night (Yeo, Hee and Heng, 2012). In the 2000s, the 'urban renaissance' trend in the West encouraged vendors to re-enter public spaces (Tiesdell and Slater, 2006;Wasserman, 2007). Even in cities with extensive regulations, street vendors or migrant workers could negotiate municipal policies or planning regulations in order to occupy public spaces (Xue and Huang, 2008;Noussia and Lyons, 2009;Yeoh and Huang, 1998).…”
Section: Governing Informality In Asiamentioning
confidence: 98%
“…Assemblages of leisure culture located in inner‐city areas have occasionally been addressed by urban scholars under the category of evening/night‐time economy (see Tiesdell and Slater, ; Shaw, ; Bøhling, ; van Liempt et al ., ), but these assemblages clearly involve more than mere economic relations. They often include creative practices, open‐ended social interaction, scene formation, emotionalized atmospheres, emergent focal places and material locations, political institution building, and more (Schwanen et al ., ).…”
Section: The Concept Of Assemblage: Imagining Urban Practicesmentioning
confidence: 99%